O princípio do contraditório e da ampla defesa no processo administrativo disciplinar - Barreto, Carolina Pereira (2013)
The research aims to study the adversarial principle and legal defense in administrative disciplinary proceedings, examined not only in its formal aspect, but also the material. For this, we start from the vision neoconstitucionalista law, especially characterized by the transformations that the rule of law and its influence on the administrative performance, highlighting the constitutionalization of administrative law as a result of this movement. At the time that will discuss the true meaning of democracy and the approximation of the relationship between state and citizen, was launched as a result of the shift in focus to administrative act administrative process. The approach will bring extensive administrative processuality sedimented as a new paradigm in consensual, citizen participation and democratic legitimacy of state activity, with the administrative process as a true instrument of positive role of government in the implementation of fundamental rights and the effective democratization of the State of Right. In this context, the research aims to deepen the study of the adversarial principle and wide defense in administrative disciplinary proceedings as a fundamental right of the citizen, serving as a tool for democratization of the state, and is in line with the new interpretation and application of the principles and values constitutional. With the effectiveness of this principle procedural constitutional guarantees to the citizen the full defense before the Disciplinary Committees, and to be effective, the defense should be performed technical point of influencing the decision of the judge in the administrative process. Thus, the discussion of the controversy will give around the analysis of the new vision of the right neoconstitucionalista, more focused on achievement of constitutional values and the effectiveness of fundamental rights, as opposed to the judicial practice of the Supreme Court, on the grounds that motivated Binding Precedent n. 05.